2020
DOI: 10.17216/limnofish.618924
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Suitability of the Fish Passages of River Ceyhan, Turkey

Abstract: The efficiencies of the two fish passages of River Ceyhan (Turkey) were investigated by using trap catches, external tags (T-bar anchor tags), PIT telemetry and radio telemetry. According to the results of the study, the pool and weir type fish passage were not effective; no fish entered the trap in this fish passage. Further, it was observed that none of the 50 external tagged fishes, 44 PIT-tagged fishes, and 47 radio-tagged fishes passed through this fish passage. A total of 900 Capoeta damascina and 520 Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…It is therefore referred to as "Yellow Fish" in the area and is significant for both reactionary and commercial fishing in streams that are connected to the river system. The C. damascina species spawns in the spring, when the males' heads are covered in tiny white reproductive tubercules (Alp et al 2020). 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is therefore referred to as "Yellow Fish" in the area and is significant for both reactionary and commercial fishing in streams that are connected to the river system. The C. damascina species spawns in the spring, when the males' heads are covered in tiny white reproductive tubercules (Alp et al 2020). 1).…”
Section: Methodsmentioning
confidence: 99%
“…C. damascina individuals in the Ceyhan and Seyhan River basins were reported as Capoeta capoeta angorae in studies conducted by Alp et al (2005). Later, taxonomic and molecular studies by Alp et al (2020), Alwan (2010), Alwan et al (2016b) and Turan et al (2022) demonstrated that the species C. angorae found in the Ceyhan and Seyhan River basins is strictly synonymous with C. damascina.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations